2022
DOI: 10.3389/fphys.2022.864758
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microvascular Senescence and Inflammation in Diabetes

Abstract: Stress-induced premature senescence can contribute to the accelerated metabolic aging process in diabetes. Progressive accumulation of senescent cells in the brain, especially those displaying the harmful inflammatory senescence-associated secretory phenotype (SASP), may lead to cognitive impairment linked with metabolic disturbances. In this context, the senescence within the neurovascular unit (NVU) should be studied as much as in the neurons as emerging evidence shows that neurogliovascular communication is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…However, generally, one of the adverse effects of NVC is hyperglycemia, i.e., the increase of glucose concentrations that determines oxidative stress contributing to endothelial and microvascular dysfunction ultimately causing neurovascular uncoupling ( Park et al, 2007 ). In fact, for example, it has been reported that endothelial cells acquire a senescent phenotype upon exposure to high glucose concentration and to other conditions that manifest in presence of metabolic disturbances (e.g., inflammation), and, consequently, this aspect also contributes to developing NVC alterations ( Phoenix et al, 2022 ). These conditions are extremely common in T2DM and may partly explain the NVC abnormalities of NVC observed in our population ( Barloese et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, generally, one of the adverse effects of NVC is hyperglycemia, i.e., the increase of glucose concentrations that determines oxidative stress contributing to endothelial and microvascular dysfunction ultimately causing neurovascular uncoupling ( Park et al, 2007 ). In fact, for example, it has been reported that endothelial cells acquire a senescent phenotype upon exposure to high glucose concentration and to other conditions that manifest in presence of metabolic disturbances (e.g., inflammation), and, consequently, this aspect also contributes to developing NVC alterations ( Phoenix et al, 2022 ). These conditions are extremely common in T2DM and may partly explain the NVC abnormalities of NVC observed in our population ( Barloese et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with cerebral small-vessel disease, damage to the cerebral WM may begin with increased BBB permeability, followed by suppression of cerebrovascular responses to CO 2 and then ischemia, 176 although other studies suggest that ischemia in watershed areas between cortical and subcortical arterial territories is the initial pathogenic event. 172,173…”
Section: The Neurovasculome In Stroke Ad and Related Dementiasmentioning
confidence: 99%
“…Of the 12 modifiable risk factors identified by the Lancet Commission with the strongest evidence for potential prevention of dementia, 9 are also risk factors for cardiovascular disease. 171 Hypertension, diabetes, smoking, obesity, and hypercholesterolemia alter neurovascular regulation 172,173 and increase the risk for dementia. 11 It is likely that neurovascular dysfunction mediates at least some of the associations of these risk factors with dementia.…”
Section: The Neurovasculome In Stroke Ad and Related Dementiasmentioning
confidence: 99%
“…127 Exposure of endothelial cells to high glucose alone can trigger a senescent phenotype. 128 In addition, retinal endothelial cells undergo premature senescence as measured by SA-β-gal positive staining following exposure to high glucose. 129 Since senescence of cells can elicit a secretory phenotype, senescence of any cell within the NVU could contribute to the neurovascular inflammation associated with AD.…”
Section: Diabetes/obesitymentioning
confidence: 99%